The yeast Wickerhamomyces anomalus acts as a predator of the olive anthracnose-causing fungi, Colletotrichum nymphaeae, C. godetiae, and C. gloeosporioides - Amorim-Rodrigues, Mariana; Brandão, Rogélio Lopes; Cássio, Fernanda; Lucas, Cândida (Frontiers in Fungal Biology, 2024)
This work aimed to evaluate the in vitro antagonistic activity and associated mechanisms of the yeast Wickerhamomyces anomalus against the fungi, Colletotrichum nymphaeae, C. godetiae and C. gloeosporioides s.s., the Olive Anthracnose causative agents prevalent in Portugal. In this work evidence is presented that W. anomalus strongly antagonises the three Colletotrichum. Antagonism was shown to not depend on the secretion of VOCs, or siderophores or any other agar-diffusible compound, including hydrolytic enzymes. Rather, it occurred mostly in a cell-to-cell contactdependent manner. Detailed microscopic assessment of yeast-fungus co-cultures showed that W. anomalus antagonism of the three Colletotrichum proceeded through (i) the adhesion of yeast cells to the phytopathogen hyphae, (ii) the secretion of a viscous extracellular matrix, and (iii) the emptying of the hyphae. Yeasts ultimately putatively feed on hyphal contents, which is supported by light microscopy observation of MB and PI co-culture-stained samples. Accordingly, numerous W. anomalus cells were observed packing inside C. godetiae emptied hyphae. This behaviour can be considered as microbial predation and classified as necrotrophic mycoparasitism, more explicit in the case of C. godetiae. Results support the prospect of applying W. anomalus as a living biofungicide/BCA in the pre-harvest control of Olive Anthracnose.